SCREENING BREAD WHEAT ENTRIES FOR FERTILE TILLERS UNDER PHOSPHORUS FERTILIZATION AND EVALUATING OF YIELD AND ITS COMPONENT FOR SUPERIOR UNDER TWO SEEDING RATES - & Kareem, Abed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The objective of this study was to know the effect of screening for the No. of fertile tillers m-2 is effective on yield in next generations. The research was conducted at field of College of Agriculture - University of Baghdad during two winter seasons, 2015-2016 and 2016-2017. Fifteen entries of wheat were introduced from CIMMYT with local variety (Abugraib3) were screened under three phosphorous rates (0, 75 and 150 kg ha-1). Superior entries in No. of fertile tillers m-2 were selected in addition to entries that gave the lowest means in this trait. In both experiments, randomized complete block design (RCBD) in split plots arrangement with three replicates was used where phosphate rates in 1st exp. and seeding rates in 2nd exp. were assigned for main plots while genotypes were in subplots. Results showed that abugraib3, G11 and G5 gave the highest means in fertile tillers m-2 (322.1, 310 and 293.3), respectively. While G14 and G13 gave the lowest means (147 and 198.4), respectively. Phosphate rate 75 kg ha-1 gave higher mean in fertile tillers per m2 than phosphate rate at 150 kg ha-1. Comparison trail results showed G13 and G11 were significantly superior in grain yield which reached 11.104 and 10.555 t ha-1, respectively. G13 and G11 gave the highest means in fertile tillers m-2 and biological yield were 759.2 and 825.8 spikes m-2 and 25.48 and 27.52 t ha-1, respectively. All genotypes planted under 160 kg seed ha-1 were decreased in spikelets spike-1 while fertile tillers m-2, grain yield, biological yield and harvest index were increased. Genotypic variance was higher than environmental variance indicating high genetic components controlling on the traits inheritance. Fertile tillers m-2 was the highest in phenotypic and genotypic variances were 2639.2 and 2610, respectively. This reflects high heritability value in broad sense was 98%. It can be concluded that screening genotypes according to No. of fertile tillers under phosphate fertilizer rates led to high potential of fertile tillers as a result of best gene expression. The best genotypes in No. of fertile tillers m-2 might be not the best in grain yield but this is related a lot with optimum seeding rate of cultivar.